IMMUNOSUPPRESSIVE EFFECTS OF ARGININE DEIMINASE FROM STREPTOCOCCUS PYOGENES - E. A. Starikova; A. V. Sokolov; L. A. Burova; I. S. Freidlin (Медицинская иммунология, 2015)
Many pathogens use metabolic pathway of arginine for successful dissemination. Bacterial arginine deiminase hydrolyzes arginine to form one molecule of ammonia and two molecules of ATP. The activity of the enzyme contributes to the improvement of survival of pathogenic bacteria in conditions of low pH at the site of infection or in phagolysosome, as well as in anaerobic conditions, and also leads to deficiency of arginine. Metabolism of arginine plays an important role in regulating the functions of immune system cells in mammals. Arginine is a substrate of enzymes NOS and arginase. Arginine depletion, potentially contributs to immunosuppression. The review analyzed the literature data on the effect of streptococcal arginine deiminase on the metabolism of arginine eukaryotic cells, and discusses immunosuppressive action of the enzyme.